A Permanent Magnet Hybrid Levitation Based on High-Temperature Superconducting Magnetic Levitation - Tianyu Xing; Lingfeng Gao; Peiyu Yin; Can Peng; Zigang Deng (Actuators)
This paper proposes an A-shape hybrid levitation system combining high-temperature superconducting (HTS) maglev and permanent magnet levitation (PML) technologies to address the lateral instability of the PML system. By tilting the PM arrays and HTS bulks on both sides at a specific angle, the system’s cross-section forms an “A” shape. This configuration offers dual advantages: the A-shape PML significantly mitigates unstable lateral deflection forces while preserving levitation capacity, whereas the A-shape HTS maglev enhances guidance force. Through systematic analysis, the effects of the tilt angle and the magnetization direction of the PM arrays on levitation performance are investigated and optimized. The simulation results demonstrate that, at the lateral movement of 5 mm, for the PML system, a tilt angle of 45° reduces lateral deflection force by 94.4%, and synergistic optimization of the tilt angle of 40° and magnetization direction of 38° achieves an 84.6% reduction. The HTS maglev system enhances guidance force, with a 45.3% improvement at a 60° tilt angle and a 30° magnetization direction. This study presents a promising solution for developing a stable, high-load-capacity hybrid levitation system.